Evaluasi Geometri Peledakan Terhadap Fragmentasi Hasil Peledakan Di Pit M Pt. Berkat Anugerah Sejahtera Job Site Pt. Multi Harapan Utama Kab. Kutai Kartanegara, Prov. Kalimantan Timur (Jurnal Geologi Pertambangan (JGP), 2022)
ABSTRAKThis activity was carried out to evaluate the planned blasting geometry with the actual blasting geometry in the field in order to produce good fragmentation so as to optimize the digging time of the PC 400 LC digging tool.The company's planned geometries include Burden (B) with a length of 5.5 to 6 meters, spacing (S) 6.5 to 7 meters, stemming (T) 2.7 meters with a blast hole depth (H) of 6.5 meters. .From the results of the study, the actual geometry with the difference in the length of the burden is -0.02 meters, the difference in spacing is -0.06 meters. So that the fragmentation value analyzed using split desktop software, namely P80 fragmentation for all locations has an average value of 65 cm, with a maximum size of 123 cm and a minimum size of 20 cm, while the digging time for all locations has an average value of 8, 11 seconds, with a maximum digging time of 13.02 seconds and a minimum digging time of 5.86 seconds. While the reference parameters used by the Company, the value of the Komatsu PC 400 LC digging time is 8-10 seconds. So it can be interpreted that the resulting fragmentation is in accordance with the digging time parameter of the Komatsu PC 400 LC loading tool. Keywords: Blasting, Fragmentation, Explosives, Blasting Geometry, Digging Time